2014
DOI: 10.1007/s11060-014-1666-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-continuous arterial spin labeling reflects vascular density and differentiates angiomatous meningiomas from non-angiomatous meningiomas

Abstract: Pseudo-continuous arterial spin labeling (PCASL) can measure tumor blood flow (TBF) reliably. We investigated meningioma TBF using PCASL and assessed for any correlation with histopathological microvascular density (MVD) and the World Health Organization (WHO) classification. Conventional MRI with contrast T1-weighted images and PCASL were acquired with a 3 T scanner before surgery in 25 consecutive patients with meningiomas. Using the PCASL perfusion map, the mean and maximum TBF were calculated from regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…ASL CBF measurements have been shown to correlate with DSC metrics in meningiomas as well as microvessel area on his-tologic specimens [19]. There also is a relationship between mengin-gioma subtype (angiomatous, meningo-epithelial, fibrous) and perfusion [9]. In that report the authors do not specify whether their method of continuous ASL could be used to differentiate meningioma grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASL CBF measurements have been shown to correlate with DSC metrics in meningiomas as well as microvessel area on his-tologic specimens [19]. There also is a relationship between mengin-gioma subtype (angiomatous, meningo-epithelial, fibrous) and perfusion [9]. In that report the authors do not specify whether their method of continuous ASL could be used to differentiate meningioma grade.…”
Section: Discussionmentioning
confidence: 99%
“…ASL has proven reliable and reproducible in the assessment of CBF in various pathological states. Correlation has been established between DSC- and ASL-derived metrics, including rCBV and CBF [8], and ASL perfusion ima-ging has been correlated with tumor blood vessel density in me-ningiomas [9]. However, the role of ASL-derived metrics as an imaging marker for differentiating benign from malignant meningiomas has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, both the mean and maximum absolute CBF values were shown to have significant positive correlations with microvascular density. 11 In this study, we investigated whether the nCBF from pseudocontinuous ASL maps could serve as a reliable imaging biomarker for angiographic vascularity of meningiomas. Our study demonstrated a significant positive correlation between the nCBF and angiographic vascularity, in keeping with the finding of the previous study, in which normalized cerebral blood volume obtained from dynamic susceptibility contrast-enhanced PWI was used.…”
Section: Discussionmentioning
confidence: 99%
“…pCASL was used by Koizumi et al 18 to differentiate angiomatous from nonangiomatous meningiomas in a study of 25 patients. The investigators found a significant correlation between the microvascular density of the meningioma and the mean and maximum total tumor blood flow.…”
Section: Tumor Meningiomasmentioning
confidence: 99%